Sustainable management of mulberry root rot using marine algal bioactive compounds - S, Anu; V M, Gayathri; P, Kirubanathy; clementina C, Mounica; Maragatham P U, Nandhini; G, Raaji; P R, Salini; B, Abinaya (Indian Journal of Plant Protection, 2026)
Seaweeds are the good source of essential nutrients, excellent eco-friendly organic manure and alternative source for inorganic chemical fertilizer for sustaining the crop yield. It is an excellent source of bioactive components with reported antimicrobial activity. The in vitro evaluation of seaweed extract against mulberry root rot has been carried out through poison food technique, agar well diffusion, and disc diffusion assays. After proper inoculation and evaluation indicated that the seaweed extract @ 10000 ppm was found to be best with 71.1 per cent mycelial inhibition and COC @ 1000 ppm was found to be 92.6 per cent mycelial inhibition. From the results of in vitro evaluation, in planta evaluation has been carried out using mulberry seedlings with 3 to 4 leaf stage. The pathogen has been pre inoculated in each seedling and symptoms observed after 24 hours of inoculation. After two days the best treatment has been inoculated through soil drenching and foliar application. It has been found that SE @ 10000 ppm has shown results with disease reduction. Even though the per cent mycelial inhibition was lower than copper oxy chloride, higher concentration may be effective against the disease incidence and safe to the environment.